The United States and right-wing dictatorships, 1965-1989 - Schmitz, David F. (Cambridge University Press, 2006)
"Building on David Schmitz's earlier work, Thank God They're on Our Side, this is an examination of American policy toward right-wing dictatorships from the 1960s to the end of the Cold War. During the 1920s, American leaders developed a policy of supporting authoritarian regimes because they were seen as stable, anticommunist, and capitalist. After 1965, however, American support for these regimes became a contested issue. The Vietnam War served to undercut the logic and rationale of supporting right-wing dictators.